Immunomagnatic Separation of E.coli O157:H7 from Raw Milk and Locally Produced Soft Cheese in Baghdad City - Khudhir, Zina Saab (The Iraqi Journal of Veterinary Medicine, 2013)
The main objectives of the present study were to assess the incidence of E .coli O157:H7 serotype in both raw milk and locally produced soft cheese samples and to evaluate the efficacy of new immunomagnetic separation (IMS) technique for the first time in Iraq for isolation of the same serotype from such products compared to the conventional cultural method .A total of 50 raw milk and soft cheese samples (25 samples of each) were collected randomly at weekly intervals from different retail markets in Baghdad province and its surroundings during the period of six months (from October 2011 March 2012). Each sample was divided into two equal parts where the first part was analyzed for the conventional cultural method and the second part was analyzed for the immunomagnetic separation technique. Five isolates (20%) and seven (28%) were identified as E.coli O157:H7 from the same raw milk samples by both the conventional cultural method and (IMS) technique respectively. Two (8%) and four isolates (16%) were identified as E.coli O157:H7 the same soft cheese samples using the same above methods. The detection limits by the conventional cultural method were 4x103 cfu/ml and 7x102 cfu/gm of raw milk and soft cheese samples respectively, while the detection limits by the (IMS) technique were 1x102 cfu/ml and 12x10 cfu/gm of raw milk and soft cheese sample respectively .Results obtained in this study revealed that the IMS technique has been recognized to be significantly (P<0.05) more efficient in its sensitivity for the detection of low numbers of E.coli O157:H7 than the direct plating conventional method for both raw milk and soft cheese samples.